Two-Direction Shear-Force sensor (2D-SFS) for measurement of friction force in structural Compression–Shear testing. (1st July 2022) - Yingri, Cao; Haishen, Wang; Jiangbo, Sun; Peng, Pan
Highlights: The articulated linking rods in 2D-SFS separates axial and shear deformation. The influence of vertical force on the 2D-SFS measurement results can be ignored. The shear measurement of 2D-SFS in two principal directions are independent. 2D-SFS effectively improves the accuracy of actual compression-shear test. Abstract: Friction forces in loading equipment can significantly affect the accuracy of results and they need to be measured in structural compression–shear tests. However, compression forces are usually much larger than the friction forces. In most structural experiments, friction forces are less than 5% of the compression forces. Thus, the shear-force sensors commonly used for mechanical applications are not suitable for this purpose. This paper presents a novel two-direction shear-force sensor (2D-SFS) to measure the boundary friction force in structural compression–shear tests. The 2D-SFS is designed to measure the force perpendicular to the compression force, thus it can measure both the friction force and the shear force, depending on the sensor location. The sensor comprises compression-force bearing components and shear-force measurement components. The compression-force bearing components have large compression stiffness and strength to sustain the compression force; the shear-force measurement components do not sustain any compression force and are used only to measure the shear force. A 2D-SFS specimen with a maximum vertical compression capacity of 20 000 kN and the measurement range of 900 kN in shear was designed and fabricated. Comprehensive error of the 2D-SFS specimen is no more than 5%. The effectiveness of 2D-SFS is verified by the compression shear test of a lead rubber bearing. The test accuracy of lead rubber bearing is effectively improved due to the horizontal force correction provided by 2D-SFS.